2022
DOI: 10.1002/ncp.10854
|View full text |Cite
|
Sign up to set email alerts
|

Improving nutrition practices for postoperative high‐risk heart transplant and ventricular assist device implant patients in circulatory compromise: A quality improvement pre– and post–protocol intervention outcome study

Abstract: Background Patients undergoing heart transplant (HT) and ventricular assist device (VAD) implant may experience intra‐ and postoperative complications requiring high‐dose vasopressor agents and/or mechanical circulatory support. These complications increase the risk of nonocclusive bowel ischemia (NOBI) and inadequate enteral nutrition (EN) delivery, and guidance for this high‐risk patient population is limited. To optimize nutrition support practices in this patient population at our institution, we created t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…Nutrient deficit improvements post-HRNSP were a result of increased exclusive and supplemental PN (SPN) utilization in the early postoperative period in the setting of inadequate EN delivery. The fewer energy and protein deficits observed after HRNSP implementation were associated with absence of NOBI cases (0%) and decreased ICU LOS ( P = 0.005) [4 ▪ ]. This study further demonstrated that optimizing MNT in heart transplant and VAD patients by adhering to institution-specific nutrition support protocols may improve patient outcomes such as the ICU LOS and occurrence of NOBI [4 ▪ ].…”
Section: Current Status Of Medical Nutrition Therapy Practices In Pat...mentioning
confidence: 59%
See 2 more Smart Citations
“…Nutrient deficit improvements post-HRNSP were a result of increased exclusive and supplemental PN (SPN) utilization in the early postoperative period in the setting of inadequate EN delivery. The fewer energy and protein deficits observed after HRNSP implementation were associated with absence of NOBI cases (0%) and decreased ICU LOS ( P = 0.005) [4 ▪ ]. This study further demonstrated that optimizing MNT in heart transplant and VAD patients by adhering to institution-specific nutrition support protocols may improve patient outcomes such as the ICU LOS and occurrence of NOBI [4 ▪ ].…”
Section: Current Status Of Medical Nutrition Therapy Practices In Pat...mentioning
confidence: 59%
“…A study by Modir et al [4 ▪ ] evaluated energy and protein intake (compared with nutrition targets) and clinical outcomes (e.g. nonocclusive bowel ischemia [NOBI], central line-associated blood-stream infection [CLABSI] rates, postoperative length of stay [LOS], mortality) in patients undergoing high-risk heart transplant and ventricular assist device (VAD) implant before and after implementing an institution-specific ‘High-Risk Nutrition Support Protocol (HRNSP)’.…”
Section: Current Status Of Medical Nutrition Therapy Practices In Pat...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the case of hemodynamic instability, PN is required. PN should be prescribed by an expert nutritionist to avoid metabolic complications such as fluid overload, overfeeding, hyperglycemia, and hypertriglyceridemia [ 118 ]. The delivery of medical nutritional therapy according to standardized protocols, preventing caloric and protein deficit, has been linked to better outcomes such as the reduced prevalence of nonocclusive bowel ischemia and reduced ICU length of stay [ 118 ].…”
Section: Fontan Failure and Heart Transplantmentioning
confidence: 99%
“…Patients undergoing cardiac surgery are at a particular risk for multifactorial hypermetabolic state and catabolic stress resulting in increased energy requirements (ER), as they regularly experience a complex systemic inflammatory response syndrome induced by factors such as surgical trauma, extracorporeal circulation, ischaemia/ reperfusion injury, haemodilution and blood loss. [1][2][3] Moreover, they are exposed to the risk of multiple organ dysfunctions requiring prolonged life-supporting treatments, resulting in prolonged mechanical ventilation and longer intensive care unit (ICU) stay. 1 In this clinical setting, possible concomitant nutritional deficits may further worsen inflammation, hypermetabolism and catabolism.…”
Section: Introductionmentioning
confidence: 99%